2005
DOI: 10.1007/s00442-005-0148-7
|View full text |Cite
|
Sign up to set email alerts
|

Marine reserves demonstrate trophic interactions across habitats

Abstract: Several infaunal bivalve taxa show patterns of decreased biomass in areas with higher densities of adjacent reef-associated predators (the snapper, Pagrus auratus and rock lobster, Jasus edwardsii). A caging experiment was used to test the hypothesis that patterns observed were caused by predation, using plots seeded with a known initial density of the bivalve Dosinia subrosea to estimate survivorship. The caging experiment was replicated at several sites inside and outside two highly protected marine reserves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Alternatively, indirect effects of fishing, such as changes in the composition of benthic communities (e.g. Shears and Babcock 2003;Langlois et al 2006b), may result in differential recruitment or habitat selection after settlement. Coralline turf, which goatfish were positively associated with, was more abundant at our non-reserve sites.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, indirect effects of fishing, such as changes in the composition of benthic communities (e.g. Shears and Babcock 2003;Langlois et al 2006b), may result in differential recruitment or habitat selection after settlement. Coralline turf, which goatfish were positively associated with, was more abundant at our non-reserve sites.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have sometimes shown that prey densities near reefs increase when predators are excluded (e.g. Posey & Ambrose 1994, Langlois et al 2006), but not always, indicating that other influences might often be more important (e.g. Jones et al 1992, Barros 2005.…”
Section: Introductionmentioning
confidence: 99%
“…However, caging experiments remain a valuable tool in predation studies of seagrass meadows (Edgar 1990;Hindell et al 2001;Moksnes et al 2008) and other marine ecosystems (Connell 1997;Sala 1997;Langlois et al 2006). It is difficult to eliminate the possibility that any effects that were detected were due to caging artefacts.…”
Section: Discussionmentioning
confidence: 99%